Writing About Oneself in a Restrictive Educational Context: Diaries, Emotional Regulation, and Creative Literacy in Islamic Boarding Schools - Laili Amalia; Adi Gunawan; Muhammad Tauhed Supratman; Ridwan Lanya; Abdul Hoffar (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study examines diary writing as a private reflective practice among female students in Islamic boarding schools characterized by strong behavioral and communication norms. Previous studies have generally positioned diary writing as either a therapeutic expressive practice or language-learning exercise. Limited attention has been given to how diary writing simultaneously functions as an emotional regulation and reflective literacy practice within highly regulated boarding-school environments. This study aimed to identify patterns of emotional regulation in students’ diary writing and examine how personal diary experiences are transformed into short fictional narratives. Using a case study diary-study design at Bahrul Huda Islamic Boarding School in Pamekasan, Indonesia, 20 female students aged 13–15 years wrote daily diaries over a one-month period. Data were collected through diary documents, perception questionnaires, and short stories developed from selected diary entries. The data were analyzed thematically, descriptively, and through genre-transfer assessment. The findings indicate that diary writing functions as a perceived safe space for emotional expression and reflective self-evaluation. Most participants demonstrated a recurring emotional pattern involving stressful experiences, emotional labelling, cathartic release, reflection, and personal resolution. However, the transfer from reflective diary writing to short-story writing remained limited, as many students produced narrative texts that were weakly connected to their original diary experiences and still dominated by report-like storytelling. This study contributes to understanding how private reflective writing mediates emotional regulation and literacy development within restrictive educational environments and highlights the importance of gradual genre scaffolding in creative writing instruction.